Analisis Pertanggungjawaban Pidana dan Penyelesaian terhadap Tenaga Medis yang Melakukan Malpraktik Medis Ditinjau dari Perspektif Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan - I Made Dwi Jayantara; Hidayattulah; Hanafi Arief (Jurnal Hukum Lex Generalis, 2024)
Medical legal regulations issued by the government are an effort to provide protection for medical personnel and patients. Medical malpractice is a complex issue that gives rise to different interpretations. According to medical personnel, it is a medical risk, while according to the patient or the victim's family, it is an act of medical malpractice. This research aims to describe the juridical analysis of medical malpractice according to Indonesian legislation. This research uses a library study method with a normative juridical approach. The research legal materials are Law Number 17 of 2023 concerning Health and various other legal regulations. The results of the study state that the regulation of medical malpractice is based on: Criminal Sanctions, Law Number 17 of 2023 concerning Health is juridically able to provide protection to medical personnel, but in its implications it has not accommodated the interests of medical personnel, has not provided a sense of justice, order, expediency, and legal certainty for medical personnel. Thus, the current regulation of medical personnel protection needs to be reconstructed. Malpractice settlement based on Indonesian legislation can be resolved by Alternative Dispute Resolution Out of Court, Restorative justice, Default, Administrative, and professional channels (Indonesian Medical Discipline Honor Council and Indonesian Medical Ethics Honor Council). But in practice it does not work well, actually this legal effort can run well if it has a Medical Dispute Resolution Institution that specifically handles issues regarding health law. Where the law enforcement officers come from people who are competent and experts in the field of health law.